Effects of coupled heat and moisture and load damage on chloride transport in concrete. Issue 13 (18th July 2022) - Min, Hongguang; Zhang, Weiping
Abstract : This paper presents thoroughgoing research on chloride transport in damaged concrete. The effects of temperature and temperature gradient on chloride transport were investigated, along with the effects of relative humidity, humidity gradient, concrete damage and exposure time. The higher the temperature and the greater the humidity gradient were, the quicker the chloride transport was. Moisture transport increased as concrete damage increased, while chloride transport decreased incrementally. Considering the effect of coupled heat and moisture on chloride transport in concrete, a chloride transport model was established and verified by experiments. Chloride profiles in damaged concrete were related to temperature, temperature gradient, relative humidity and humidity gradient. The chloride attack rate decreased with increasing concrete damage and exposure time. Hence, coupled heat and moisture as well as concrete damage had significant effects on chloride transport in damaged concrete, and the effects of concrete damage on chloride transport should be considered when determining chloride profiles in damaged concrete.